2022
DOI: 10.1055/s-0042-1750839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Parameters on Outcomes of Lumbar Microdiscectomy: A Retrospective Analysis

Abstract: Objective The objective of this study was to characterize the effect of preoperative variables on outcomes after minimally invasive lumbar microdiscectomy. Materials and Methods This study was done from January 2019 to May 2020. This included medical records of all patients who were diagnosed with lumbar disc herniation and treated surgically by microdiscectomy. The medical records of such patients from January 2016 to January 2018 were included in this study. Postoperative outcomes were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In line with previous research, no significant effect of sex or age on the magnitude of postoperative pain relief was found [ 7 , 13 , 15 ]. A few previous studies from the same research team have suggested that older age and female sex might predict worse outcome of microdiscectomy [ 12 , 15 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous research, no significant effect of sex or age on the magnitude of postoperative pain relief was found [ 7 , 13 , 15 ]. A few previous studies from the same research team have suggested that older age and female sex might predict worse outcome of microdiscectomy [ 12 , 15 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Microsurgical excision of herniated lumbar intervertebral disc is a widely accepted generally safe and often effective treatment to ease back and leg pain intensity and disability severity [ 1 7 ]. However, while multiple studies have reported significant improvement after the procedure concerning both the severity of pain and the level of disability, it has usually been reported that the procedure might affect radicular leg pain more substantially than local back pain.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous research, no signi cant effect of gender or age on the magnitude of postoperative pain relief was found [7,13,15]. Few previous studies from the same research team have suggested that older age and female gender might predict worse outcome of microdiscectomy [12].…”
Section: Discussionsupporting
confidence: 88%
“…Microsurgical excision of lumbar intervertebral disc displacement is a widely accepted generally safe and often effective treatment to ease back and leg pain [1][2][3][4][5]. Multiple studies have reported signi cant improvement after the procedure concerning both the severity of pain and the level of disability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of ineffectiveness of conservative measures for resolve patient clinical symptoms, a microsurgical discectomy using is used to remove the herniated intervertebral disk (IVD) and decompress the symptomatic nerve [3]. It was found that after lumbar discectomy have risk for symptom recurrence, loss of disc height with postoperative radiculopathy and reoperation associated with recurrent herniation [4,5].…”
Section: Introductionmentioning
confidence: 99%